Case Report: Spontaneous Postpartum Quadruple Cervicocephalic Arterial Dissection With a Heterozygous COL5A1 Variant of Unknown Significance - Imamura, Takeaki; Omura, Takaki; Sasaki, Nobuo; Arino, Satoshi; Nohara, Haruna; Saito, Akira; Ichinose, Maki; Yamaguchi, Kazumasa; Kojima, Naoki; Inagawa, Hiroshi; Takahashi, Katsutoshi; Unno, Toshiyuki; et al. (Frontiers in Neurology, 2022)
Pregnancy-associated cervicocephalic arterial dissection is rare, and its pathophysiology remains poorly understood. Despite the hypothesized contribution to pathogenesis, connective tissue diseases and genetic factors are rarely identified in clinical cases. We describe a case of postpartum arterial dissection involving all four cervicocephalic arteries resulting in acute cerebral infarction. The patient underwent successful endovascular thrombectomy and angioplasty and recovered fully without sequelae. Genetic screening for connective tissue diseases identified a heterozygous missense COL5A1 variant with unknown clinical significance. Two genetically related family members later developed arterial abnormalities, and one of them tested positive for the same COL5A1 gene variant as our patient, while the other was scheduled for genetic testing. The extensive clinical presentation of our patient and the prevalence of arterial abnormalities in her family warrant further assessment of the association between the identified COL5A1 gene variant and the pathogenesis of arterial dissections.